An Erythrocyte Membrane-Associated Antigen, PvTRAg-26 of Plasmodium vivax: A Study of Its Antigenicity and Immunogenicity - Liping Fan; Jinxing Xia; Jilong Shen; Qiang Fang; Qiang Fang; Hui Xia; Hui Xia; Meijuan Zheng; Jin-Hee Han; Eun-Taek Han; Bo Wang; Yuanhong Xu (Frontiers Media S.A., 2020)
Background:Plasmodium tryptophan-rich (TR) proteins have been proposed as potential vaccine candidate antigens. Among them, P. vivax tryptophan-rich antigens (PvTR-Ags), which have positionally conserved tryptophan residues in a TR domain, are highly antigenic in humans. Several of these antigens, including PvTRAg-26, have exhibited erythrocyte-binding activities.Methods: Subclasses of IgG antibodies against PvTRAg-26 were detected by enzyme-linked immunosorbent assay in 35 P. vivax infected patients and mice immunized with the recombinant antigen to characterize its antigenicity and immunogenicity. Moreover, the antigen-specific immune responses and Th1/Th2-type cytokine patterns of splenocytes from the immunized animals were determined in vitro. The subcellular localization of PvTRAg-26 in ring-stage parasites was also detected by indirect immunofluorescence assay.Results: The IgG1 and IgG3 levels in P. vivax-infected patients were significantly higher than those in uninfected individuals. In the PvTRAg-26-immunized mice, elevated levels of antigen-specific IgG antibodies were observed, dominated by the IgG1 subclass, and Th1-type cytokines were remarkably increased compared with Th2-type cytokines. Additionally, the subcellular location of the PvTRAg-26 protein was closely associated with the caveola-vesicle complex on the infected-erythrocyte membrane in the early ring stage of P. vivax.Conclusions: PvTRAg-26, a P. vivax TR antigen, with high antigenicity and immunogenicity, induces Th1-cytokine response and increases production of IgG1 antibodies. This immune profiling study provided a substantial evidence that PvTRAg-26 may be a potential candidate for P. vivax vaccine development.